THE RELATIONSHIP PARENT’S ATTENTION, AND LEARNING ENVIRONMENT IN SCHOOL AND LEARNING MOTIVATION WITH MATHEMATICS LEARNING OUTCOMES IN STUDENTS CLASS VIII OF SMP MUHAMMADIYAH BANTUL - Devi Eka Murningsih; Suparyan Suparyan (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2017)
Low student learning outcomes associated with many factors. The relationship parent’s attention, and learning environment in school and learning motivation are some of the factors possibly related to learning outcomes. This research aims to determine the presence or absence of positive and significant relationship parent’s attention, learning environment in school and learning motivation with mathematics learning outcomes in students class VIII of SMP Muhammadiyah Bantul in odd semester in the academic year of 2016/2017. The population in this research was the students of  VIII grade in SMP Muhammadiyah Bantul in the academic year of 2016/2017, consisted of class  VII A, VIII C, VIII D, VIII E totaling 145 students. Samples were taken from VII A as the research sample class and with the random sampling technique. The writer uses a questionnaire method to collect the data of parent’s attention, learning environment in school and learning motivation and test method to get the resulting learning of math. The research instrument: validity test, different power test, and reliability test. Test requirement analysis includes a test of normality, a test of linearity, and the test of independence. The writer uses product-moment correlation analysis and multiple linear regression analysis to analyze the data. The results showed that there was a positive and significance relationship parent’s attention, learning environment in school and learning motivation with mathematics learning outcomes in students class VIII in odd Semester of SMP Muhammadiyah Bantul in academic year of 2016/2017. It is showed by Fcount  Ftable is 6,2645 > 2.98 with R = 0.6477 and R2 = 0.4196 with , with SR  , SR  and SR , SE , SE  and SE .